Fear no evil [large type] - Patterson, James, 1947- (Patterson, James, 1947- Alex Cross series, 2021)
"Alex Cross enters the final battle with the all-knowing genius who has stalked him and his family for years. Dr. Alex Cross and Detective John Sampson venture into the rugged Montana wilderness--where they will be the prey. They're not on the job, but on a personal mission. Until they're attacked by two rival teams of assassins, controlled by the same mastermind who has stalked Alex and his family for years. Darkness falls. The river churns into rapids. Shots ring out through the forest. No backup. No way out. Fear no evil."--